Hubungan Konsumsi Kerang Dengan Tekanan Darah Pada Masyarakat Pesisir - Basudewa, I Nyoman Arhi; Setyawan, Yuswanto (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Shellfish are an important source of nutrition for coastal communities but may also pose potential health risks if consumed excessively. The aim of this study was to analyze the association between shellfish consumption and blood pressure as well as cardiovascular profile among coastal communities. Methods: This research employed an observational analytic design with a cross-sectional approach. The study population consisted of coastal residents aged 25–60 years, with a total sample of 135 respondents selected using purposive sampling. The independent variable was shellfish consumption, while the dependent variable was blood pressure. Data were collected through structured interviews and blood pressure measurement using a sphygmomanometer. Data analysis was performed using the Chi-Square test for categorical associations and Spearman correlation for continuous variables. Results showed a significant relationship between frequency of shellfish consumption and blood pressure (p < 0.05), indicating that moderate shellfish consumption was associated with a more stable blood pressure profile. Conclusion: Shellfish consumption may provide cardiovascular benefits; however, the frequency and quantity of intake should be carefully considered to avoid hypertension risks due to high sodium content. Keywords: Shellfish, Consumption, Blood Pressure, Hypertension, Cardiovascular